Miniaturized Ceramic-Based Microbial Fuel Cell for Efficient Power Generation From Urine and Stack Development - Gajda, Iwona; Stinchcombe, Andrew; Merino-Jimenez, Irene; Pasternak, Grzegorz; Sanchez-Herranz, Daniel; Greenman, John; Ieropoulos, Ioannis A. (Frontiers in Energy Research, 2018)
One of the challenges in Microbial Fuel Cell (MFC) technology is the improvement of the power output and the lowering of the cost required to scale up the system to achieve usable energy levels for real life applications. This can be achieved by stacking multiple MFC units in modules and using cost effective ceramic as a membrane/chassis for the reactor architecture. The main aim of this work is to increase the power output efficiency of the ceramic based MFCs by compacting the design and exploring the ceramic support as the building block for small scale modular multi-unit systems. The comparison of the power output showed that the small reactors outperform the large MFCs by improving power density, reaching up to 21 mW/m3. This can be related to the increased surface-area-to-volume ratio of the ceramic vessel, which also acts as a membrane with a decreased electrode distance. The miniaturised design implemented in a 560 MFC unit stack, gave an output of up to 245 mW of power and being increased in power density can utilise the energy locked in the urine at a high rate, with increased efficiency, making MFCs more applicable in industrial and municipal wastewater treatment facilities, and scale-up-ready for real world implementation.